Pengaruh Citra Merek dan Desain Produk Terhadap Keputusan Pembelian Mobil Honda Jazz di Kota Tasikmalaya: Suatu Analisis Survei pada Konsumen Produk Mobil Honda Jazz - Djordan, Adam Muhammad; Tri Yusnita, Rita; Sutrisna, Arga (Awatara Publisher, 2023)
This research explores the influence of brand image and product design on the purchasing decisions of Honda Jazz in Tasikmalaya City, Indonesia, within the competitive automotive industry context. A multiple linear regression analysis indicates that brand image and product design significantly positively impact purchasing decisions. A good brand image and appealing product design are associated with increased purchasing decisions. Recommendations are provided for Honda Jazz manufacturers and marketers to continuously maintain brand image and innovate in design to retain consumer loyalty and attract potential consumers in the competitive automotive market. This study narrows its focus to consumers in Tasikmalaya City, and highlights the importance of brand image and product design in consumer purchasing decisions within the automotive industry.